Effect of Endodontic Irrigation on the Bond Strength of Composite Restoration Repair - Latife Altınok Uygun; Ahmet Demirhan Uygun; Seray Doğan; Mustafa Mertcan Deliktaş; Ali Çınar (Applied Sciences)
This study aims to evaluate the effect of endodontic irrigation solutions on the bond strength of composites subjected to different aging procedures. Using a shear bond strength test, the effects of sodium hypochlorite (NaOCl), ethylenediaminetetraacetic acid (EDTA), and chlorhexidine (CHX) solutions on composite–composite bond strength were examined. The findings revealed that NaOCl alone significantly reduced bond strength, while its adverse effect was completely reversed by the subsequent application of EDTA. CHX, when applied after NaOCl or in combination with EDTA, provided only partial improvement. An aging procedure (5000 thermal cycles) did not have a statistically significant impact on the bond strength. This study provides valuable insights into the roles of endodontic irrigation solutions in composite repair and their implications for restorative dentistry. These findings underline the clinical relevance of selecting appropriate irrigation protocols to preserve or improve bonding during the repair of composite restorations after endodontic treatment.